Dynamic physiological responses in obese and non-obese adults submitted to cardiopulmonary exercise test - Gonze, Bárbara de Barros; Ostolin, Thatiane Lopes Valentim Di Paschoale; Barbosa, Alan Carlos Brisola; Matheus, Agatha Caveda; Sperandio, Evandro Fornias; Gagliardi, Antônio Ricardo de Toledo; Arantes, Rodolfo Leite; Romiti, Marcello; Dourado, Victor Zuniga (PLOS ONE, 2021)
Purpose Obese individuals have reduced performance in cardiopulmonary exercise testing (CPET), mainly considering peak values of variables such as oxygen uptake (V˙O2), carbon dioxide production (V˙CO2), tidal volume (Vt), minute ventilation (V˙E) and heart rate (HR). The CPET interpretation and prognostic value can be improved through submaximal ratios analysis of key variables like ΔHR/ΔV˙O2, ΔV˙E/ΔV˙CO2, ΔV˙C/Δlinearized (ln)V˙E and oxygen uptake efficiency slope (OUES). The obesity influence on these responses has not yet been investigated. Our purpose was to evaluate the influence of adulthood obesity on maximal and submaximal physiological responses during CPET, emphasizing the analysis of submaximal dynamic variables. Methods We analyzed 1,594 CPETs of adults (755 obese participants, Body Mass Index ≥ 30 kg/m2) and compared the obtained variables among non-obese (normal weight and overweight) and obese groups (obesity classes I, II and III) through multivariate covariance analyses. Result Obesity influenced the majority of evaluated maximal and submaximal responses with worsened CPET performance. Cardiovascular, metabolic and gas exchange variables were the most influenced by obesity. Other maximal and submaximal responses were altered only in morbidly obese. Only a few cardiovascular and ventilatory variables presented inconsistent results. Additionally, Vtmax, Vt/V˙E, Vt/Inspiratory Capacity, Vt/Forced Vital Capacity, Lowest V˙E/V˙CO2, ΔV˙E/ΔV˙CO2, and the y-intercepts of V˙E/V˙CO2 did not significantly differ regardless of obesity. Conclusion Obesity expressively influences the majority of CPET variables. However, the prognostic values of the main ventilatory efficiency responses remain unchanged. These dynamic responses are not dependent on maximum effort and may be useful in detecting incipient ventilatory disorder. Our results present great practical applicability in identifying exercise limitation, regardless of overweight and obesity.